Non-contact neuromodulation of the human autonomic nervous system function via different odors: Sex, menstrual cycle, and odor dose- and duration-specific effects - Maharjan, Ashim; Khwaounjoo, Prashanna; Peng, Mei; Cakmak, Yusuf Ozgur (Frontiers in Neuroscience, 2022)
In recent decades, it has been uncovered that the autonomic nervous system (ANS), in particular the parasympathetic-vagal network, can be influenced using non-contact neuromodulation via odor stimulation. Increasing parasympathetic-vagal activation of the ANS is integral in improving the sympathovagal balance between the sympathetic- and parasympathetic nervous systems which is often imbalanced in several chronic inflammatory disorders such as rheumatoid arthritis, Crohn’s disease and inflammatory bowel disease. Although research into olfactory stimulation has been observed on the ANS, it is still lacking in the exploration of odor concentration and odor-specific effects. This is particularly the case as research has not utilised specified tools such as the olfactometer to provide precise odor delivery. Furthermore, no research has compared the results in separate sex cohorts to investigate the role of sex or menstrual stage on the subsequent interactions. In this study, we investigated the olfactory stimulation effects of four natural odors (mushroom, lavender, jasmine and rose) in three concentrations (low, moderate and high) on the ANS. To observe activity from the ANS, we used an electrocardiogram (ECG) and eye-tracker technology (pupil dilation). We found for the first time in literature, that there were dose- and duration-specific odor effects of odors on the ANS. We also found sex and menstrual cycle effects in this interaction. In the male cohort, olfactory stimulation with a high concentration of rose odor increased the parasympathetic activation of the ANS (p-value = 0.008; Cohen’s D - 0.43, small effect size) whereas, in the female cohort, repetitive presentation of rose odor, irrespective of odor concentration, increased the parasympathetic activation of the ANS in only the luteal-menstrual stage (p-value = 0.044; Cohen’s D - 0.17, small effect size). Furthermore, there were stark distinctions in the vagus-dependent (ECG) ANS activation in comparison to the occulomotor/cervical-dependent ANS (eye-tracker). Vagus-dependent ANS showed odor, sex and menstrual-stage interactions in both divisions of the ANS whilst eye-tracker only indicated increased sympathetic activation independent of sex and menstrual-stage. These results shed light on the use of odour specific stimulation to modulate the parasympathetic-vagal network of the ANS in the context of sex and the menstrual stage.